2019
DOI: 10.15252/embj.2018100907
|View full text |Cite
|
Sign up to set email alerts
|

A non‐death function of the mitochondrial apoptosis apparatus in immunity

Abstract: Apoptosis is a frequent form of programmed cell death, but the apoptotic signaling pathway can also be engaged at a low level, in the absence of cell death. We here report that such sub‐lethal engagement of mitochondrial apoptosis signaling causes the secretion of cytokines from human epithelial cells in a process controlled by the Bcl‐2 family of proteins. We further show that sub‐lethal signaling of the mitochondrial apoptosis pathway is initiated by infections with all tested viral, bacterial, and protozoan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 47 publications
3
88
0
Order By: Relevance
“…However, we have found that under conditions of sub‐lethal stress, a limited number of mitochondria in a cell can undergo permeabilisation, called minority MOMP, leading to genomic instability and transformation . A recent report by Brokatsky et al reveals a link between pathogen invasion and activation of mitochondrial cell death machinery . In this study, it was found that various pathogens can induce limited mitochondrial permeabilisation.…”
Section: Introductionmentioning
confidence: 52%
“…However, we have found that under conditions of sub‐lethal stress, a limited number of mitochondria in a cell can undergo permeabilisation, called minority MOMP, leading to genomic instability and transformation . A recent report by Brokatsky et al reveals a link between pathogen invasion and activation of mitochondrial cell death machinery . In this study, it was found that various pathogens can induce limited mitochondrial permeabilisation.…”
Section: Introductionmentioning
confidence: 52%
“…In addition, classical apoptosis mainly encompasses the mitochondrial and death receptor pathways, of which the mitochondrial pathway is closely related to changes in intracellular mitochondrial transmembrane potential [60]. CCM@MSNs-ISOIM was found to reduce the intracellular mitochondrial transmembrane potential in NHL, and CCM@MSNs-ISOIM was also observed to significantly increase ROS levels in NHL, further suggesting that CCM@MSNs-ISOIM may induce apoptosis through the intracellular mitochondrial apoptosis pathway.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, classical apoptosis mainly encompasses the mitochondrial and death receptor pathways, of which the mitochondrial pathway is closely related to changes in intracellular mitochondrial transmembrane potential [74]. CCM@MSNs-ISOIM was found to reduce the intracellular mitochondrial transmembrane potential in NHL, and CCM@MSNs-ISOIM was also observed to significantly increase ROS levels in NHL, further suggesting that CCM@MSNs-ISOIM may induce apoptosis through the intracellular mitochondrial apoptosis pathway.…”
Section: Discussionmentioning
confidence: 96%